Effect of Parenting on Stunting Incidence in Infant Aged 0-59 Months Old - Andi Surahman Batara; Idhar Darlis (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Parenting is a factor most significantly affect and contribute to the incidence of stunting in infants aged 0-59 months. Parenting has recently attracted many attentions since parents are the one who have the most interaction with their own children. Hence, current research was carried out to know the correlation between parenting and the incidence of stunting in infants aged 0-59 months. Methods: This research was carried out through quantitative method with cross sectional approach. In this case, the samples involved are 169 infants. The data obtained were further analyzed through logistic regression with the assistance of SPSS Version 26. Results: There is a relationship between parenting and the incidence of stunting in infants aged 0-59 months old with the logistic regression P-value of <0.05.59,8% respondent of them received poor parenting and his education is only senior high school and This finding found that the higher the knowledge of parents, the more it will influence the provision of food to their children with good nutritional value. Conclusion: Parenting on the incidence of stunting in infants aged 0-59 months old is very important. In this case, knowledge and nutritional intake are necessary to support the growth and development of infants aged 0-59 months.